Internal Rating Systems and the Bank-Firm Relationship Valuing Company Networks - Quattrociocchi, Bernardino (Palgrave Macmillan Studies in Banking and Financial Institutions, 2016)
This book provides the conceptual and operational tools for understanding the mechanisms for assigning a rating to a network of companies. In it, the author explores the rating systems of corporate networks and analyses the link between rating and an enterprise network.